The effectiveness of educational design design according to the theory of Ozbal in the acquisition of geographical concepts among the pupils of the fourth primary in the geography and development of their habits of mind (Journal Of Educational and Psychological Researches, 2018)
Summary The objective of the research is to learn the design of a learning educational learning according to the theory of Ausubel in the acquisition of geographical concepts among the students of the fourth primary in the field of geography and the development of their habits of mind. To achieve this, the researcher relied on the two hypotheses the researcher used the design of equal groups the first experimental group was studied according to the design educational educational learning according to the theory and the other is an officer according to the traditional method. The research community consists of fourth grade pupils in primary school day for girls in the Directorate of Education Baghdad, Al-Rusafa, the third academic year 2015-2016. The research sample included (51) where the school of Abdullah bin Abbas represented the experimental group and the number of its students was 25 students. The new generation school was represented by the group of officers and the number of its pupils was 26 pupils. The school consisted of two elementary schools that were deliberately chosen from among the original community schools, Abdullah bin Abbas and the new generation. The researcher prepared a first test to measure the acquisition of concepts included 20 paragraphs of the type of multiple choice and the second measure of the measurement of the habits of the mind consists of (50 paragraphs) distributed on (16) usually and after the statistical treatment with data using the test For two independent samples, the results were as follows: 1 - The pupils of the experimental group that studied the design of learning educational learning according to the theory of Ausubel students in the control group, which studied the usual way to acquire concepts 2 - The superiority of the students of the experimental group studied the design of learning educational learning according to the theory of Ausubel students in the control group in the habits of the mind